Observations of the gamma-ray-emitting narrow-line Seyfert 1, SBS 0846+513, and its host galaxy - Hamilton Timothy S; Berton Marco; Antón Sonia; Busoni Lorenzo; Caccianiga Alessandro; Ciroi Stefano; Gässler Wolfgang; Georgiev Iskren Y; Järvelä Emilia; Komossa S; Mathur Smita; Rabien Sebastian (OXFORD UNIV PRESS, 2022)
The gamma-ray-emitting galaxy SBS 0846+513 has been classified as a narrow-line Seyfert 1 (NLS1) from its spectroscopy, and on that basis would be thought likely to have a small central black hole hosted in a spiral galaxy. However, very few of the gamma-ray NLS1s have high-resolution imaging of their hosts, so it is unknown how the morphology expectation holds up for the gamma-emitting class. We have observed this galaxy in the Jband with the Large Binocular Telescope's LUCI1 camera and the ARGOS adaptive optics system. We estimate its black hole mass to lie between 4.2 x 10(7) <= M/M-circle dot <= 9.7 x 10(7), using the correlation with bulge luminosity, or 1.9 x 10(7) <= M/M-circle dot <= 2.4 x 10(7) using the correlation with Sdrsic index. Our favoured estimate is 4.2 x 10(7) M-circle dot, putting its mass at the high end of the NLS1 range in general but consistent with others that are gamma-ray emitters. These estimates are independent of the broad-line region viewing geometry and avoid any underestimates due to looking down the jet axis. Its host shows evidence of a bulge + disc structure, from the isophote shape and residual structure in the nuclear-subtracted image. This supports the idea that gamma-ray NLS1 may be spiral galaxies, like their non jetted counterparts.